Diagnosis and localization of the maxillary impacted canines by using dental multi-slice computed tomography 3D view and reconstructed panoramic 2D view - Nadia B Al-Ansari; Nidhal H Ghaib; Shifaa H Al-Naimi (College of Dentistry/ University of Baghdad, 2014)
Background: Diagnosis and treatment planning can be difficult with conventional radiographic methods as the orthodontic-surgical management of impacted canines requires accurate diagnosis and precise localization of the impacted canine and the surrounding structures. This study was aimed to localize and evaluate weather there is any differences in the diagnostic information provided by multi-slice computed tomography three dimensional volumetric CT images and two dimensional reconstructed panorama images (derived from CT) in subjects with impacted maxillary canines. Materials and Methods: Thirty patients including 24 female and 6 male with mean age of 18 years with suspected unilaterally or bilaterally impacted maxillary canines were evaluated on images taken with Brilliance 64, Philips multi-detector computed tomography. The spatial relationships of the impacted maxillary canines relative to the adjacent structures was evaluated using linear and angular measurements, and the adjacent lateral incisor root resorption was assessed with three dimensional and two dimensional visualization software. Results: The inclination of the impacted maxillary canine measured to the midline and to the occlusal plane did not differ significantly when it was evaluated using the two imaging modalities. However, there were significant differences between the 3D and 2D images with respect to the impacted maxillary canine vertical height, bucco-palatal localization, and in detecting the proximity and root resorption of the adjacent lateral incisors. Conclusion: Dental CT volumetric images provide more reliable and accurate information for diagnosing the maxillary impacted canine position, inclination, distance from adjacent structures, and detection of lateral incisors rootresorption.